Studying disruptive events: Innovations in behaviour, opportunities for lower carbon transport policy?. (August 2020) - Greg Marsden,; Jillian Anable,; Chatterton, Tim; Docherty, Iain; Faulconbridge, James; Murray, Lesley; Roby, Helen; Shires, Jeremy
Abstract: The continued failure to put transport on a robust low carbon transition pathway calls for new approaches in policy and research. In studies of transport systems and patterns of mobility, established approaches to data collection, analysis and subsequent policy design have focused on capturing 'typical' conditions rather than identifying the potential for substantive change. This focus on the apparent aggregate stability of the transport regime has reproduced a belief in policy circles that our current travel patterns are largely fixed and therefore very difficult to alter, which in turn has resulted in an over reliance on implausible assumptions about the carbon reductions that can be achieved through technological improvements such as low emission vehicles. This paper argues that there is potentially much greater adaptive capacity in the mobility system than currently allowed for. It illustrates this potential through the investigation of actual adaptations made during a set of specific 'disruptive' events. The paper concludes by suggesting that we can go further in reducing the demand for travel if we broaden the scope of intervention to take a wider view of when and how mobility matters to participation in activities across the population. This could enable an acceleration of existing trends which suggest the potential for less mobility and therefore less carbon intensive lives. Highlights: Data collected during episodes of transport 'disruption' offer novel insights on behavioural adaptations. The learnings from responses to 'disruptions' are important for understanding the potential for policy change. Transport patterns are not as difficult to change as is commonly understood.